A Two-Step TLS-Based Browser fingerprinting approach using combinatorial sequences. Issue 114 (March 2022) - Garn, Bernhard; Zauner, Stefan; Simos, Dimitris E.; Leithner, Manuel; Kuhn, Richard; Kacker, Raghu
Highlights: Browser Fingerprinting. TLS Protocol. Combinatorial Sequences. Graphical abstract: Abstract: We propose a two-step TLS-based fingerprinting approach using combinatorial sequences and properties of TLS handshake messages. Our approach combines fingerprinting based on attributes of the initial ClientHello message with the observed behavior of TLS clients when presented with permuted handshake messages in order to enhance the granularity of the derived fingerprints without increasing the required number of exchanged messages. We conduct a detailed evaluation against 21 browsers and TLS clients on two operating systems. The results show a significant increase in the entropy of the achieved splittings, allowing for a more precise identification of the TLS client than permitted by either of the underlying approaches in isolation.